Electrochemical behavior of guidewires made of X10CrNi 18-8 STEEL - W. Walke (Metalurgija, 2013)
The purpose of this study was to evaluate corrosion resistance of wires with differentiated of surface preparation and with differentiated work hardening, used in low-invasive cardiology in sterile environment. The study is devoted to voltamperometric and impedance tests, which were used to determine typical features describing corrosion resistance. Measurement system PGSTAT 302n together with a set of measurement electrodes were used for the tests. The tests were carried out in artificial blood plasma at the temperature of T = 37 °C. Obtained results were used as the ground for selecting the way of preparation of the surface of X10CrNi 18-8 steel in order to improve its biotolerance in blood environment.